Perancangan Aplikasi Mixed Reality Shagy (Sheila Art Gallery) Berbasis Android Menggunakan ARCore - Lastri Pratiwi; Sumi Khairani; Nur Wulan (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
Along with the development of information and communication technology, there are more and more facilities that can facilitate a person in all things. One of the developing technologies is Mixed Reality. one of the arts that is currently in great demand is painting, but painting exhibitions in Medan City are still very minimal and not in demand so every time there is a painting exhibition there are very few visitors and that can cause quite large losses, then not all painters have the money to build their own art gallery. One application that uses Mixed Reality technology is an application for Sheila Art Gallery’s artwork, another name is Mixed Reality Shagy. With the Shagy (Sheila Art Gallery) application, art gallery application users can be more interested in the works of art on display, and can understand more about the background and meaning of the works of art. Researchers built a 3D model of the artwork on diplay at the Sheila Art Gallery. This Application is carried out the provide an alternative virtual art gallery experience to users. This application can help artists promote their work to the wider community through interactive experiences. This broadens the scope of art promotion and creates closer relationships between artist and users.